Association of Dental Caries with Body Mass Index in Patients Attending Dental OPD of Armed Forces Institute of Dentistry: A Cross-Sectional Study - Khurshid, Talha; Rana, Nadeem Ahmad; Shah, Muzammil Hussain; Naqvi, Syed Shan e Haider; Abdullah, Ahmed; Rehman, Zainab Ur (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the association of carious lesions with body mass index (BMI) using the International Caries Detection and Assessment System (ICDAS) system. Study Design: Analytical cross-sectional study. Place and Duration of Study: Armed Forces Institute of Dentistry, Rawalpindi, Pakistan from Mar to Aug 2024. Methodology: A total of 104 subjects were evaluated for this study with BMI of each participant grouped into four BMI categories: underweight, normal, overweight and obese, and ICDAS system was used for caries detection. Descriptive statistics were evaluated in Microsoft Excel and statistical analysis was done between BMI and dental using Fisher’s exact test where a p-value < 0.05 was considered as statistically significant. Results: Mean BMI among males was 32.69±8.58 kg/m2 and among females was 25.06±5.15 kg/m2. Code 00 was not observed and codes 03, 04, 21, 31, 52 and 62 were most frequently found ICDAS codes among the subjects. A statistically significant difference (p-value <0.001) in the distribution of ICDAS scores across all BMI categories (underweight, normal, overweight, and obese) was observed. Conclusion: ICDAS score was highest among obese subjects and a positive association was observed between dental caries and BMI.